An unusual skin reaction in uveal melanoma during treatment with nivolumab: extragenital lichen sclerosus. Issue 9 (October 2019) - Veronesi, Giulia; Scarfì, Federica; Misciali, Cosimo; Tartari, Federico; Melotti, Barbara; Patrizi, Annalisa; Dika, Emi
Abstract : Antibodies directed against programmed death receptor 1 emerged as beneficial immune-checkpoint inhibitor therapy in many different types of cancer. However, programmed death receptor 1 is critical in promoting self-tolerance and the most common toxicities of checkpoint inhibitors are immune-related adverse events. We present a 48-year-old woman affected by metastatic uveal melanoma treated with nivolumab (3 mg/kg every 2 weeks). The patient had no previous history of autoimmune disease or dermatologic conditions. At the fourth month of treatment, on cutaneous examination, she presented multiple whitish vitiligo-like patches on the trunk, axillae, hands and face. Diagnosis of melanoma-associated leukoderma vitiliginous reaction was made. Over the following months, the melanoma-associated leukoderma lesions slowly progressed with cigarette paper-like appearance and indurated texture. A skin biopsy leaded the diagnosis of extragenital lichen sclerosus. To the best of our knowledge, this is the first reported case of extragenital lichen sclerosus on previous melanoma-associated leukoderma lesions related to nivolumab monotherapy. The increase in clinical experience with anti programmed death receptor 1 enhances the knowledge about adverse effects associated with these immunotherapies and allows to compare therapeutic strategies.